Martian Atmospheric Spectral End‐Members Retrieval From ExoMars Thermal Infrared (TIRVIM) Data. Issue 9 (9th September 2022) - Alemanno, G.; D'Amore, M.; Maturilli, A.; Helbert, J.; Arnold, G.; Korablev, O.; Ignatiev, N.; Grigoriev, A.; Shakun, A.; Trokhimovskiy, A.
Abstract: Key knowledge about planetary composition can be recovered from the study of thermal infrared spectral range datasets. This range has a huge diagnostic potential because it contains diagnostic absorptions from a planetary surface and atmosphere. The main goal of this study is to process and interpret the dataset from the Thermal Infrared channel (TIRVIM) which is part of the Atmospheric Chemistry Suite of the ExoMars2016 Trace Gas Orbiter mission to find and characterize dust and water ice clouds in the atmosphere. The method employed here is based on the application of principal component analysis and target transformation techniques to extract the independent variable components present in the analyzed dataset. Spectral shapes of both atmospheric dust and water ice aerosols have been recovered from the analysis of TIRVIM data. The comparison between our results with those previously obtained on Thermal Emission Spectrometer (TES) data and with previous analysis on TIRVIM data, validates the methodology here applied, showing that it allows to correctly recover the atmospheric spectral endmembers present in the TIRVIM data. Moreover, comparison with atmospheric retrievals on PFS, TES and IRIS data, allowed us to assess the temporal stability and homogeneity of dust and water ice components in the Martian atmosphere over a time period of almost 50 years. Plain Language Summary: The analysis of thermal infrared datasets from planetary bodies is of key importance for the understanding of a planet's climate evolution and history: it contains valuable information about composition, temperature and state of the atmosphere. Moreover, surface properties and the surface‐atmosphere interaction can be studied. Here we investigated new thermal infrared data from the Thermal Infrared channel instrument of the ExoMars Trace Gas Orbiter with the main goal of carefully identifying Martian atmospheric dust and water ice clouds components. A methodology based on principal component and target transformation factor analysis techniques has been applied. Based on our results, this methodology can correctly recover both atmospheric dust and water ice aerosols spectral shapes and their abundances in the Martian atmosphere. Key Points: First successful application of principal components and target transformation techniques to high‐resolution Thermal Infrared channel (TIRVIM) data Spectral shapes of both atmospheric dust and water ice clouds are recognized and recovered TIRVIM data are successfully modeled through a linear combination of the recovered water ice and dust end‐members